O Mal em Anticristo de Lars Von Trier: considerações sobre o mal, a teodiceia e o gnosticismo - Arielo, Flávia Santos (2013)
The investigation regarding the existence of evil in the world is confused by human existence. This investigation presents itself in a natural way to the theological world, practically referring to all religions-taking into consideration that the definition of good and evil are present in all of them. Also, in the philosophical field, from the Greek to the Contemporary, this is a theme that triggered many speeches and theories. The goal of this dissertation is to evaluate the evil from the cinematographic art, specifically using the film Antichrist, from the Danish director Lars Von Trier. For that reason, Philosophers and Theorists will be quoted from each religion that relates to the theme. With the unfolding of film plot, besides the evil, another two other references will be discussed: Theodicy and Gnosticism. Both the movie and the theme of evil allow for further reading and questioning of these tow concepts. It is indispensable to study those who try to justify God in respect to the evil in the world, hence the Theodicy theme, developed by the philosopher Leibniz, and that kept being debated for centuries. The Gnosticism starts the discussion from the cosmogenic and anthropogenic concepts. Viewed as one of the cults form primitive Christianity, Gnosticism spreads that the creation of the world and man was the act of an evil God. The analysis of the movie in question allows, through questioning in the characters dialogues and scenes, the relating of the problem of evil, Theodicy and Gnosticism in the world created by the Danish director